Tool use aids prey-fishing in a specialist predator of stingless bees - Zhaoyang Chen; Li Tian; Jin Ge; Shiyu Wang; Ting Chen; Yuange Duan; Fan Song; Wanzhi Cai; Zhengwei Wang; Hu Li (Proceedings of the National Academy of Sciences, 2025)
Tool use is widely reported across a broad range of the animal kingdom, yet comprehensive empirical tests of its function and evolutionary drivers remain scarce, predominantly focused on a few relatively intelligent vertebrate lineages. In this study, we provide a comprehensive examination of tool use behavior in the assassin bug Pahabengkakia piliceps , a specialist predator of stingless bees that exploits resin droplet from bee nest entrance to facilitate hunting. Field behavioral experiments demonstrated that resin use is critical for hunting success, as the predator uses resin to stimulate the colonial defense of stingless bees, luring attacking bees toward its optimal hunting position. Chemical analysis revealed that resin processing by the assassin bug enhances the emission of volatile compounds, making the resin more attractive and stimulating to guard bees. Through these experiments, we empirically demonstrate how an invertebrate predator adapts to the colony defense of social insects via tool use behavior. We further propose that complex tool use can evolve under selective pressures driven by diet specialization. Our findings offer a new model for studying the adaptive functions and underlying mechanisms of tool use behaviors in animals.